If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 4 + -3x + 2 = 41 Reorder the terms: 4 + 2 + 8x + -3x = 41 Combine like terms: 4 + 2 = 6 6 + 8x + -3x = 41 Combine like terms: 8x + -3x = 5x 6 + 5x = 41 Solving 6 + 5x = 41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5x = 41 + -6 Combine like terms: 6 + -6 = 0 0 + 5x = 41 + -6 5x = 41 + -6 Combine like terms: 41 + -6 = 35 5x = 35 Divide each side by '5'. x = 7 Simplifying x = 7
| 8m+3=16 | | f(x)=ln(8x) | | 25a-8b+4c-6a+13b-c= | | 2a+12+a+(3a-9)=117 | | 6-18=m-4+14 | | (-3x^2-2x-2)+(2x^2+4x+4)= | | 9p-4p=-7 | | 27=3/7+6 | | 9x-4=65 | | 6+c=18 | | 3w+15=-4(w-2) | | 3w+15=-(w-2) | | 5-(1-x)=20 | | 7x+5y=-16 | | x=3(y/9) | | (4x^2+3x-5)(2x^3-10x+11)= | | 6x-15=6x | | 2x+7=10x+9 | | a-4/9a=-7/9 | | 1/2x^3-1/2x^2-24=0 | | 7=-2n-5 | | p(x)-750x^2+15000x=0 | | 0.8(25m-20n)= | | 5(2n-1)=5 | | -6+2t=3t-(6+5) | | 3x=y/9 | | ((d-4)/4)^2=49 | | -102=-6(8n+1) | | 2(3-6n)=102 | | 3[m+(-5)]=2m+10 | | 30+-10= | | 5-4(8x-2)=0 |